Surveillance of ADHD Among Children in the United States: Validity and Reliability of Parent Report of Provider Diagnosis. Issue 2 (January 2023) - Cree, Robyn A.; Bitsko, Rebecca H.; Danielson, Melissa L.; Wanga, Valentine; Holbrook, Joseph; Flory, Kate; Kubicek, Lorraine F.; Evans, Steven W.; Owens, Julie Sarno; Cuffe, Steven P.
Objective: To evaluate the appropriateness of parent-reported diagnosis of ADHD as a surveillance tool. Method: We assessed agreement over time and concordance of parent-reported diagnosis against Diagnostic and Statistical Manual (DSM)-based criteria. We compared concordance of diagnosis and DSM-based criteria by child characteristics, including treatment. Results: Among parents who reported their child had ADHD, 95.7% reported it again 2 years later. Comparing diagnosis with DSM-based criteria, specificity and negative predictive value were high, sensitivity was moderate, and positive predictive value was low. Most children with an ADHD diagnosis who did not meet DSM-based criteria met sub-threshold criteria or took medication for ADHD. Concordance differed by child characteristics and treatment. Conclusion: Parent-reported diagnosed ADHD is reliable over time. Although differences in parent-reported diagnosis and DSM-based criteria were noted, these may reflect children with milder symptoms or treated ADHD. Parent-report of child ADHD ever diagnosis may be a good single-item indicator for prevalence.